Innovation policies in the European news and media industry : a comparative study - Kranenburg, Hans van (Springer, 2017)
This book explores the importance and the types of media innovation policies formulated and implemented in various European countries. Each country analysis illustrates the evolution and structure of news media markets and media cross-ownership policies in recent years and evaluates how innovation policies stimulate innovative activities in journalism and news media. The main objective of this book is to promote discussion on how innovation policies can help the news media industry to meet development needs and requirements in the future. It will help scholars, politicians and practitioners in the media industry to identify best practices to support innovation in a rapidly changing news media landscape.
1 Market Structure and Media Ownership.
Keywords: Mass media policy -- Europe.; Mass media -- Technological innovations -- Europe.; Mass media -- Economic aspects -- Europe.; elektronické knihy; electronic books